Antagonistic Activities of Selected Bacterial Isolates Against Soilborne Disease Pathogens of Turfgrass - Che Mohd. Ramli, Neni Kartini (1999)
Disease samples exhibiting symptoms of brown patch, yellow patch and Pythium blight were taken from several golf courses in Malaysia Isolation and identification of the pathogens indicated that Rhizoctonia solani Kuhn, Rhizoctonia cerealis Van der Hoeven and Pythium aphanidermatum (Edson) Fitzpatrick were the causal agents respectively. Identification of the pathogens was based on their morphological characteristics. Isolation of bacteria from thatch resulted in the isolation of ten bacterial isolates of which five were found to be antagonistic against the pathogens. The bacterial isolates were identified as Burkholderia cepacia (syn. Pseudomona. cepacia), Serratia marcescens, Chromobacterium violaceum, Pseudomonas aeruginosa and Bacillus megaterium. B.cepacia, P. aeruginosa and B. megaterium were found to